Persepsi Mahasiswa mengenai Fee Auditor, Nilai Sosial dan Lingkungan Keluarga terhadap Pilihan Karirnya sebagai Auditor (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the perceptions of accounting students in public and private universities in Purwokerto regarding the factors that influence their career choices as auditors. The factors examined include auditor fees, social values, and family environment. This research employs a descriptive quantitative approach with a cross-sectional survey design. Data were collected through questionnaires distributed to 160 accounting students who had completed auditing courses. The sampling technique used was purposive sampling. The results of multiple linear regression analysis show that auditor fees (X1) do not have a significant effect on students’ career choices as auditors. Although financial compensation is considered, it is not the main determinant of students’ career decisions. Social values (X2) have a positive and significant influence on students’ career choices as auditors. Students’ positive perceptions of the social status, reputation, interaction opportunities, and professional expertise of auditors significantly increase their tendency to pursue this career. The family environment (X3) also has a positive and significant effect on students’ career choices as auditors. Moral support, motivation, facilities, and family expectations play an important role in shaping students’ career preferences in the field of auditing. Simultaneously, auditor fees, social values, and family environment have a significant influence on students’ career choices as auditors. This indicates that students’ career decisions are the result of a combination of financial, social, and family support factors that complement one another.